2015
DOI: 10.1007/978-3-319-15582-1_22
|View full text |Cite
|
Sign up to set email alerts
|

Is RPL Ready for Actuation? A Comparative Evaluation in a Smart City Scenario

Abstract: Abstract. Low-power wireless actuation is attracting interest in many domains, yet it is significantly less investigated than its sensing counterpart, especially in large-scale scenarios. As a consequence, guidelines about which protocol, among the few existing ones, is best suited to a given scenario are generally lacking. In this paper, we investigate the relative performance of simple disseminationbased solutions against the standard, state-of-the-art RPL protocol. These choices of protocols are motivated c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 10 publications
0
21
0
Order By: Relevance
“…The noise floor was set to 90dBm with a standard deviation of 2dBm. These values were shown to be realistic for low noise environments in [9].…”
Section: Simulationmentioning
confidence: 99%
See 1 more Smart Citation
“…The noise floor was set to 90dBm with a standard deviation of 2dBm. These values were shown to be realistic for low noise environments in [9].…”
Section: Simulationmentioning
confidence: 99%
“…Similar questions have attracted increased attention in the recent literature, e.g. in [9,10] 2 and [19]. Perhaps equally important are the questions: can both collect and control tra c types e↵ectively coexist in a full network stack, what is the relationship between them, and what are the inherent trade-o↵s?…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the RPL standard does not specify the action to take after a parent refuses to install a new downward route (e.g., because its routing table is full), therefore undermining the reliability of downward traffic. We recently analyzed the problem in our own work, where we focused on emulation of the Contiki RPL implementation over realistic topologies taken from a smart city deployment [12]. Figure 3 illustrates the problem: the reliability of downward traffic (e.g., for actuation) decreases severely as soon as the size of the network approaches the size of the routing table, which we set to 50 entries-the maximum allowed on TMote Sky, as already discussed.…”
Section: Scalabilitymentioning
confidence: 99%
“…Therefore, the route discovered is the shortest path in a tree. However, a recent study by Istomin et al (2015) showed that RPL is not ready to handle P2P communication required in actuation networks and its strength lies in its collection capabilities [28].…”
Section: A Routing Table Discoverymentioning
confidence: 99%